ANALISIS KESALAHAN DAN KONSTRASTIF DALAM PEMBELAJARAN BAHASA ARAB - Nandang Sarip Hidayat (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
Error analysis and contrastive language is one step to overcome the language learners in language errors. Error analysis is a way of speaking or working step commonly used by the researcher or teacher to collect data, identify errors, explain the error, classify and evaluate the level of seriousness of the fault errors that occurred in the language berbahasa. Kesalahan language learners in general can be grouped in the form of error interlingual ( الأخطاء التطورية ), intralingual errors ( الأخطاء داخل اللغة ), a global error ( الكليالأخطاء ) and local faults ( الأخطاء الجزءي .) while contrastive analysis is comparing the activities of linguists in the source language and the target language either makrolinguistik or mikrolinguistik to find differences and equations both languages. The purpose of the error analysis and contrastive language is to have theoretical and applicative purposes, which in practice requires certain steps, such as data collection, identification of errors and contrastive language itself, and can be found errors and kontrastifnya, repaired and eventually in the applicable order, the learners language (students) have the right language and can speak well